Edukasi Entrepreneurship: Membangun Pola Berfikir Santri di Pesantren Al Furqon Cisarua - Syaodih, Erliany; Sustariyah, Sri; Sritumini, Bella Annantha (Jurnal Pengabdian Tri Bhakti, 2023)
The high economic needs in people's lives today are a condition that cannot be avoided. Santri, as part of society, cannot be separated from these demands, so they need to prepare themselves for their economic resilience. Al-Furqon Islamic Boarding School with students who come from people with limited economic capabilities is a pesantren that focuses on learning only on religious-based knowledge. All daily operational costs are funded by donors and community sympathizers, making it vulnerable to financial problems. Based on the existing problems, a solution is needed from academics to help the Al Furqon Islamic boarding school to become an economically independent pesantren and not only depend on donors. An effective way which is at the same time the development of an educational companion program at the Al-Furqon Islamic boarding school is to provide education about entrepreneurship both to the students as well as the pesantren administrators. The first educational activity will be directed at efforts to change or improve the mindset (pattern) of students' thinking in entrepreneurship, followed by skills training and discussion.